Functional odor map heterogeneity is based on multifaceted glomerular connectivity in larval Xenopus olfactory bulb - Offner, Thomas; Weiss, Lukas; Daume, Daniela; Berk, Anna; Inderthal, Tim Justin; Manzini, Ivan; Hassenklöver, Thomas; Justus Liebig University Giessen (My University, 2023)
Glomeruli are the functional units of the vertebrate olfactory bulb (OB) connecting olfactory receptor neuron (ORN) axons and mitral/tufted cell (MTC) dendrites. In amphibians, these two circuit elements regularly branch and innervate multiple, spatially distinct glomeruli. Using functional multiphoton-microscopy and single-cell tracing, we investigate the impact of this wiring on glomerular module organization and odor representations on multiple levels of the Xenopus laevis OB network. The glomerular odor map to amino acid odorants is neither stereotypic between animals nor chemotopically organized. Among the morphologically heterogeneous group of uni- and multi-glomerular MTCs, MTCs can selectively innervate glomeruli formed by axonal branches of individual ORNs. We conclude that odor map heterogeneity is caused by the coexistence of different intermingled glomerular modules. This demonstrates that organization of the amphibian main olfactory system is not strictly based on uni-glomerular connectivity.
Keywords: ddc:570